2009
DOI: 10.1371/journal.pone.0005392
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Anti-β-Glucan Antibodies Is Associated with Restricted β-1,3 Glucan Binding Specificity and Inhibition of Fungal Growth and Adherence

Abstract: Anti-β-glucan antibodies elicited by a laminarin-conjugate vaccine confer cross-protection to mice challenged with major fungal pathogens such as Candida albicans, Aspergillus fumigatus and Cryptococcus neoformans. To gain insights into protective β-glucan epitope(s) and protection mechanisms, we studied two anti-β-glucan monoclonal antibodies (mAb) with identical complementarity-determining regions but different isotypes (mAb 2G8, IgG2b and mAb 1E12, IgM). C. albicans, the most relevant fungal pathogen for hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
191
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(207 citation statements)
references
References 93 publications
12
191
1
3
Order By: Relevance
“…Interestingly, only a minimal rise in antibody to b-glucan was found, suggestive that antibodies play a minimal role in protection (Clemons et al, 2014b). The latter is in opposition to the studies using laminarin conjugated to diphtheria toxoid, which suggested antibody directed against b-glucan was a major mechanism of protection against multiple fungal infections ( Torosantucci et al, 2005Torosantucci et al, , 2009). As we noted previously, induction of the various pro-inflammatory cytokines and chemokines is suggestive of a priming of an active innate immune response, whereas increases in IFNc and IL-17 suggest an induction of a cell-mediated immune response (Zelante et al, 2009;Clemons et al, 2014b;Whibley & Gaffen, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, only a minimal rise in antibody to b-glucan was found, suggestive that antibodies play a minimal role in protection (Clemons et al, 2014b). The latter is in opposition to the studies using laminarin conjugated to diphtheria toxoid, which suggested antibody directed against b-glucan was a major mechanism of protection against multiple fungal infections ( Torosantucci et al, 2005Torosantucci et al, , 2009). As we noted previously, induction of the various pro-inflammatory cytokines and chemokines is suggestive of a priming of an active innate immune response, whereas increases in IFNc and IL-17 suggest an induction of a cell-mediated immune response (Zelante et al, 2009;Clemons et al, 2014b;Whibley & Gaffen, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…However, in the past decade, a series of studies done with a family of V region identical isotype switched Abs to Cryptococcus neoformans polysaccharide using monovalent peptide mimetics provided strong evidence for C-mediated effects on V region function as manifested by isotype-related differences in specificity and affinity (9)(10)(11)(12). In addition, two other groups, including the report by Tudor et al (5), described additional examples in which Abs expressing identical V region sequences manifested altered specificity and/or affinity (13). Given that five independent groups have now reported that C region can affect V region affinity and/or specificity (5,7,8,10,13)…”
Section: Region Can Affect V Regionmentioning
confidence: 99%
“…In addition, two other groups, including the report by Tudor et al (5), described additional examples in which Abs expressing identical V region sequences manifested altered specificity and/or affinity (13). Given that five independent groups have now reported that C region can affect V region affinity and/or specificity (5,7,8,10,13)…”
Section: Region Can Affect V Regionmentioning
confidence: 99%
“…For example, when incubated with C. neoformans, 2G8(IgG2b) prevents capsule formation and reduces capsule size (Hole and Wormley 2012). 2G8 has also been found to be fungistatic against Candida albicans and prevent its attachment to human epithelial cells in vitro (Phan et al 2007;Torosantucci et al 2009;Dwivedi et al 2011). The efficacy of 2G8 in vivo has shown therapeutic promise in mouse models of pulmonary cryptococcosis, as well as invasive and vaginal candidiasis (Torosantucci et al 2009;Capodicasa et al 2011;Hole and Wormley 2012).…”
Section: Antibody Therapymentioning
confidence: 99%